Studying the photocatalytic oxidation of hydroxybenzene in aquatic medium on the photocatalizers SnO₂, ZnO, TiO₂ - Deineka, D. M.; Kobziev, Oleksandr; Avina, Svitlana; Grin, Svitlana; Deyneka, Viktoriya; Taraduda, Dmytro; Sobina, Vitaliy (Технологический центр, 2018)
This paper reports results of research into photocatalytic activity of oxides SnO₂, ZnO, TiO₂ in the process of hydroxybenzene degradation in an aqueous medium with the separately considered properties of the allotrope modifications of titanium oxide (IV): anatase and rutile. The relationship has been substantiated between a decrease in the value for the width of the restricted area and an increase in the photocatalytic activity of the examined oxides. The effect has been established of the organization of agitation on an increase in the degree of hydroxybenzene degradation in an aqueous medium, which is 10‒15 % on average. We have studied the influence of ratio of anatase to rutile in a photocatalyst on the hydroxybenzene degradation efficiency. It has been shown that the results obtained in the course of the study are consistent with data from the scientific literature, while opening up additional possibilities to increase the degree of hydroxybenzene oxidation in a joint application of anatase and rutile. It was established that the greatest degree of oxidation with and without agitation at an irradiation time of 60 minutes can be achieved at the content ratio of anatase to rutile of 75/25 % and is 23 % and 37 %, respectively. The use of such a composition makes it possible to increase the degree of hydroxybenzene oxidation in an aqueous medium by 11‒18 %, which is 1.5‒1.9 times larger in comparison with pure rutile and anatase. The results obtained led to the conclusion on that in order to reduce the time required to achieve the maximal indicators for the process of hydroxybenzene degradation, it is necessary to increase the ratio of the irradiated surface to the height of the device and to increase the Re number of the agitation process. Based on the obtained experimental data, we have established the optimum composition of a photocatalyst, which makes it possible to reach the maximal degree of hydroxybenzene recovery from solution.

Наведено результати дослiдження фотокаталiтичної активностi оксидiв SnO₂, ZnO, TiO₂ в процесi окиснення гiдроксибензолу у водному середовищi, окремо розглянуто властивостi алотропних модифiкацiй оксиду титану (IV): анатазу та рутилу. Обґрунтовано взаємозв'язок зменшення значення ширини забороненої зони та збiльшення фотокаталiтичної активностi розглянутих оксидiв. Встановлено вплив органiзацiї перемiшування на зростання ступеня деградацiї гiдроксибензолу у водному середовищi, яке становить в середньому 10–15 %. Дослiджено вплив спiввiдношення вмiсту анатазу до рутилу у фотокаталiзаторi на ефективнiсть деградацiї гiдроксибензолу. Показано, що отриманi при цьому результати дослiджень узгоджуються з лiтературними даними, але вiдкриваються додатковi можливостi збiльшення ступеня окиснення гiдроксибензолу прi сумiсном використаннi анатазу та рутилу. Встановлено, що найбiльший ступiнь окиснення з перемiшуванням та без нього при часi опромiнювання 60 хвилин досягається при спiввiдношеннi кiлькостi анатазу до рутилу 75/25 % мас. та складає 23 % i 37 %, вiдповiдно. Використання такого складу дозволяє збiльшити ступiнь окиснення гiдроксибензолу у водному середовищi на 11–18 %, що в 1,5–1,9 разiв бiльше порiвняно з чистим рутилом та анатазом. Показано, що при використаннi фотокаталiзатора iз сумiшi анатазу та рутилу характер впливу перемiшування на ступiнь окиснення гiдроксибензолу має iншу закономiрнiсть, нiж при використаннi чистого анатазу або рутилу. Одержанi результати дозволили зробити висновок, що для скорочення часу досягнення максимальних показникiв процесу деградацiї гiдроксибензолу необхiдно збiльшувати вiдношення поверхнi опромiнювання до висоти самого апарату та збiльшувати число Re процесу перемiшування. На основi отриманих експериментальних даних встановлено оптимальний склад фотокаталiзатору, який дозволяє досягти максимальний ступiнь вилучення гiдроксибензолу iз розчину.
Вивчення фотокаталітичного окиснення гідроксибензолу у водному середовищі на фотокаталізаторах SnO₂, ZnO, TiO₂
Keywords: wastewater treatment; hydroxybenzene; photocatalytic activity; titanium dioxide; anatase; rutile; очищення стiчних вод; гiдроксибензол; фотокаталiтична активнiсть; оксид титану; анатаз; рутил